2007
DOI: 10.1002/ird.320
|View full text |Cite
|
Sign up to set email alerts
|

Spatial productivity along a canal irrigation system in Pakistan

Abstract: This study was undertaken to investigate the impact of location on productivity of the farmers along an irrigation network in Pakistan. Data were collected from 54 tertiary canals situated along six secondary canals: two each at the head, middle and tail end of the main canal. Results revealed that location of the farms has a significant impact on farmers' productivity on different reaches along all the irrigation channels, i.e. the main canal, the secondary and the tertiary canals. The productivity of the tai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 8 publications
0
24
1
Order By: Relevance
“…However, the survey showed that (at least some of) the farmers in the tail end reaches still had the opportunity to gain high profits -sometimes even higher than those in the head end reaches -by shifting to high-value cash crops, mainly luffah and grapes. Such findings contrast with numerous studies (e.g., El-Shinnawi et al 1980;Skold et al 1984;Perry and Narayanamurthy 1998;Brugere and Lingard 2003;Latif 2007;Sharma et al 2008;Molle et al 2010;Venot et al 2010) that showed a decrease in high-value crops, cultivated areas and incomes as one moves downstream.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…However, the survey showed that (at least some of) the farmers in the tail end reaches still had the opportunity to gain high profits -sometimes even higher than those in the head end reaches -by shifting to high-value cash crops, mainly luffah and grapes. Such findings contrast with numerous studies (e.g., El-Shinnawi et al 1980;Skold et al 1984;Perry and Narayanamurthy 1998;Brugere and Lingard 2003;Latif 2007;Sharma et al 2008;Molle et al 2010;Venot et al 2010) that showed a decrease in high-value crops, cultivated areas and incomes as one moves downstream.…”
Section: Discussioncontrasting
confidence: 54%
“…On the other hand, social and economic sciences have addressed the equity issues of top-down projects and policies (e.g., El-Shinnawi et al 1980;Skold et al 1984;Wichelns 1998;Wichelns 2000;Wichelns 2002;Hussain et al 2003). For example, ElShinnawi et al (1980), Skold et al (1984), Bhattarai et al (2002), Brugere and Lingard (2003), Latif (2007), and Aruna Shantha and Ali (2013) identified an income gap between the upper and lower reaches of the canal, which is due to the large share of water used by farmers at the head end of the canal to the detriment of those at the tail end. The differences in water availability, inequity in water distribution, and the impacts of inadequate irrigation on yields and farmers' income have been well documented in Egypt and in many other arid and semiarid regions (e.g., El-Shinnawi et al 1980;Skold et al 1984;Brugere and Lingard 2003;Tyagi et al 2005;Bekchanov et al 2010;El-Agha et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Past experience shows that this package, although broadly beneficial to societies, has not yet fully succeeded in banishing poverty (Hussain, 2007). The extensive review suggests that there are strong linkages between irrigation and poverty (Hussain and Hanjra, 2004;Latif, 2007). Multicriteria decision making models are developed for irrigation planning and irrigation scenarios are used to show the impact of different irrigation management (Max et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…But poor performance, inefficiency and inequality of the irrigation system may not be effective in overcoming poverty, as happened in Pakistan [6]. Thus income o the farmers and their poverty can be directly related to the performance of irrigation systems, as is demonstrated in recent studies by Latif [7], Hussain et al [8], Bhattarai et al [9]. The main objective of this article is to demonstrate that quality of groundwater, soil salinity, cost of pumping groundwater and income of the farmers vary along the irrigation canals in Pakistan.…”
Section: Introductionmentioning
confidence: 99%